Sustainable Intensification in Smallholder Agriculture 2017
DOI: 10.4324/9781315618791-13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring options for sustainable intensification through legume integration in different farm types in Eastern Zambia

Abstract: Sustainable intensification has recently been developed and adopted as a key concept and driver for research and policy in sustainable agriculture. It includes ecological, economic and social dimensions, where food and nutrition security, gender and equity are crucial components. This book describes different aspects of systems research in agriculture in its broadest sense, where the focus is moved from farming systems to livelihoods systems and institutional innovation.Much of the work represents outputs of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These four case study farms were simulated with FarmDESIGN, a bio-economic farm model that calculates the impacts of various farm configurations on a large set of agro-environmental and socio-economic performance indicators. Applications of FarmDESIGN in the Netherlands (Mandryk, Reidsma, Kanellopoulos, Groot, & van Ittersum, 2014), Zambia (Timler, Michalscheck, Alvarez, Descheemaeker, & Groot, 2017), and Mexico (Cortez-Arriola et al, 2014, 2016Flores-Sanchez et al, 2011) have suggested the model is robust enough to accommodate contrasting farming systems and agro-ecologies. FarmDESIGN has been evaluated in terms of design-, output-and end-user validity.…”
Section: Participatory Bio-economic Modelling and Multi-objective Optmentioning
confidence: 99%
“…These four case study farms were simulated with FarmDESIGN, a bio-economic farm model that calculates the impacts of various farm configurations on a large set of agro-environmental and socio-economic performance indicators. Applications of FarmDESIGN in the Netherlands (Mandryk, Reidsma, Kanellopoulos, Groot, & van Ittersum, 2014), Zambia (Timler, Michalscheck, Alvarez, Descheemaeker, & Groot, 2017), and Mexico (Cortez-Arriola et al, 2014, 2016Flores-Sanchez et al, 2011) have suggested the model is robust enough to accommodate contrasting farming systems and agro-ecologies. FarmDESIGN has been evaluated in terms of design-, output-and end-user validity.…”
Section: Participatory Bio-economic Modelling and Multi-objective Optmentioning
confidence: 99%
“…It is the main staple, providing 52% of the local population’s daily calorie intake [ 2 ]. Maize is regarded as an economic and political crop in Zambia due to enabling maize production across the country [ 3 ]. Approximately 80% of Zambian smallholder households and 20% of commercial farmers grow maize.…”
Section: Introductionmentioning
confidence: 99%
“…Four case study farms were simulated with FarmDESIGN, a bio-economic farm model that calculates the impacts of various farm configurations on a large set of agro-environmental and socio-economic performance indicators. Applications of FarmDESIGN in the Netherlands (Mandryk et al, 2014), Zambia (Timler et al, 2017), and Mexico (Cortez-Arriola et al, 2014Flores-Sanchez et al, 2011Groot et al, 2016) have suggested the model is robust enough to accommodate contrasting farming systems and agro-ecologies. FarmDESIGN has been evaluated in terms of design-, output-and end-user validity.…”
Section: Bio-economic Modelingmentioning
confidence: 99%